"On the Whole We Don't:" Michel Foucault, Veena Das and Sexual Violence. Issue 2 (3rd May 2016) - Deutscher, Penelope
Abstract : Foucault's analysis of biopolitics has been appraised by Didier Fassin as successfully recognizing an essential trait of contemporary society: the attribution of an absolute value to abstract life and the emergence of political governmentalities managing life. Yet, claims Fassin, Foucault overlooked the need for paying close analytical attention to the everyday detail of lives differentially rendered worth living. Giving a focus to anthropologist Veena Das's work on sexual violence, this paper considers the surprising use by a number of contemporary post-Foucauldian theorists of the resources made available by philosopher Stanley Cavell's reading of Wittgenstein as an alternative for the analysis of everyday violence. Having discussed a further tenor of criticism of Foucault – suggestions that the articulation of biopolitics and its forms of indirect murder as a general phenomenon fail to describe the prior or framing conditions under which certain human lives are more vulnerable than others to becoming disposable life – the paper reconstructs a new lexicon of terms devised by Das which would be more adequate to such analysis. In fact, the paper argues that Foucault is just as available for such reconfiguration as other theorists to whom Das responds differently.